2018
DOI: 10.1002/elsc.201800077
|View full text |Cite
|
Sign up to set email alerts
|

Microbial production of d‐lactic acid from dried distiller's grains with solubles

Abstract: d‐Lactic acid production is gaining increasing attention due to the thermostable properties of its polymer, poly‐d‐lactic acid . In this study, Lactobacillus coryniformis subsp. torquens, was evaluated for its ability to produce d‐lactic acid using Dried Distiller's Grains with Solubles (DDGS) hydrolysate as the substrate. DDGS was first subjected to alkaline pretreatment with sodium hydroxide to remove the hemicellulose component and the generated carbohydrate‐rich solids were then subjected to enzymatic hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Dried Distillers Grains with Solubles (DDGS) was supplied from a bioethanol plant (Vivergo, Yorkshire, UK) and was alkaline pretreated as described by Zaini et al [28]. Alkaline treated DDGS consisted of 52.6 g glucose, 25.0 g xylose, 10.3 g arabinose, and 0.04 g protein per 100 g of dried material.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dried Distillers Grains with Solubles (DDGS) was supplied from a bioethanol plant (Vivergo, Yorkshire, UK) and was alkaline pretreated as described by Zaini et al [28]. Alkaline treated DDGS consisted of 52.6 g glucose, 25.0 g xylose, 10.3 g arabinose, and 0.04 g protein per 100 g of dried material.…”
Section: Methodsmentioning
confidence: 99%
“…D-lactic acid was produced by L. coryniformis subsp. torquens (DSM 20004) using a Simultaneous Saccharification and Fermentation (SSF) process of alkaline treated DDGS in a 2 L stirred tank bioreactor (Biostat B, Sartorious, Germany) [28]. The process was initiated by the simultaneous addition of Accellerase® 1500 (1 ml enzyme : 0.33 g cellulose) and L.…”
Section: D-lactic Acid Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, their high acidity is easy to cause environmental pollution. At present, distiller's grains are mainly consumed as cheap animal feed, which produces very low economic benefits (Zaini et al ., 2019). Therefore, how to improve the comprehensive utilisation and increase the added value of distiller's grains is a great challenge for the spirits industry.…”
Section: Introductionmentioning
confidence: 99%
“… However, to achieve high lactic acid yields (g lactic acid per g sugar), SSF carried out in fed‐batch mode is demonstrated to be the preferred strategy. Thus, fed batch SSF has been efficiently applied to obtain second‐generation lactic acid from a vast range of raw material such as NaOH‐pretreated corn stover, ethylenediamine pretreated rice straw, alkaline pretreated dried distiller's grains or cheese whey powder, amongst others . All of these studies demonstrated that the SSF approach resulted in faster and higher production of d ‐lactic acid compared to conventional SHF.…”
Section: Introductionmentioning
confidence: 99%